2011
DOI: 10.3382/ps.2010-01104
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salmonella spp. in feces, cloacal swabs, and eggs (eggshell and content separately) from a laying hen farm

Abstract: Microbial pathogens of the genus Salmonella are among the leading causes of foodborne illness in the world. The present study was done on a laying hen farm with a Salmonella enterica serovar Enteritidis-positive result according to the testing specified by European regulation 2160/2003. The aim of this study was to compare the Salmonella contamination on a laying hen farm with the Salmonella presence in the hen eggs. The strains were isolated by ISO method 6579:2002 (standard method for the detection of Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 21 publications
8
22
5
Order By: Relevance
“…This is relatively high compared to the results of other researchers [28,29,17] who demonstrated prevalence rates of 4% 19% and 26.3% respectively from poultry cloacal swabs. The relatively high prevalence rate of Salmonella from cloacal swabs as recorded by this study suggests that high number the poultry birds in Calabar are infected with the Salmonella species.…”
Section: Discussioncontrasting
confidence: 50%
“…This is relatively high compared to the results of other researchers [28,29,17] who demonstrated prevalence rates of 4% 19% and 26.3% respectively from poultry cloacal swabs. The relatively high prevalence rate of Salmonella from cloacal swabs as recorded by this study suggests that high number the poultry birds in Calabar are infected with the Salmonella species.…”
Section: Discussioncontrasting
confidence: 50%
“…detection by CB in cloacal swabs (1.6%) were lower than those reported by Singh et al (2013), who have found 4.4%, and by García et al (2011), which 4% of cloacal swabs were positive for this bacteria. Cloacal swabs used as samples to monitor the presence of Salmonella by conventional bacteriology present limitations.…”
Section: Resultscontrasting
confidence: 51%
“…from chicken faecal samples in Owerri metropolis Imo state, Nigeria. However, Garcia et al (2011) reported a lower isolation rate of Salmonella from laying hens in Aquidauana, Brazil. The results obtained in this study were consistent with the reports of other studies carried out in other parts of the world (Akond et al, 2012).…”
Section: Discussionmentioning
confidence: 97%